Absorptive CdTe films optical parameters and film thickness determination by the ellipsometric method - Evmenova, Anna Z.; Odarych, Volodymyr A.; Sizov, Fedir F.; Vuichyk, Mykola V. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
Ellipsometric detective method of refractive index, absorptive index and thickness of the film deposited on the substrate with some optical parameters has been developed. This method is applied for optical parameters and film thickness detecting in visible and near IR spectrum. Refraction index and film thickness dispersion has been studied. It has been determined that film refractive index (2.6 on average) is by 7% less than that of monocrystalline CdTe.
Optica Applicata, Vol. 38, 2008, nr 3, s. 585-600
Keywords: optyka; ellipsometry; passivation CdTe films; methods of calculating film parameters